The night before summer vacation - Wing, Natasha; Durrell, Julie (New York : Grosset & Dunlap, 2002)
In the style of Clement Moore's familiar Christmas poem, tells of a family's last minute preparations for summer vacation.
Accelerated Reader AR
Keywords: Family recreation -- Juvenile poetry; Vacations -- Juvenile poetry; Children's poetry, American; Vacations -- Poetry; Family life -- Poetry; American poetry